Basic discussions of Urdu linguistics: اُردو لسانیات کے بنیادی مباحث - Jundran, Dr. Azeemullah; Ovaisi, Dr. Muhammad Arshad (Al Khadim Research Journal of Islamic Culture and Civilization, 2023)
This research paper envisages the overview of linguistics. Linguistic study was limited to only the historical and comparative study of languages prior to the establishment of Pakistan. Then, it was focused upon the only explanatory of study of languages. Only those dictionaries came into being whose orientation was majorly textural. Urdu and Persian dictionaries played an important role in the dissemination of urdu linguistics before the existence of Pakistan. Structuralism, stylistics, Formalism and phonology also got promotion in that era. The commendable services of the orientalists cannot be overlooked in this regard.